Research on vertical deformation and predeformation control of three‐tower connected super high‐rise structure during construction. (2nd December 2021) - Yuan, Zhijie; Sun, Guangjun; Wu, Xiaoping; Li, Hongjing; Kong, Lei
Summary: Connected super high‐rise structure has a long construction period and significant time‐dependent characteristics, so it is necessary to study its vertical deformation during construction. Taking an asymmetrical three‐tower conjoined super high‐rise structure as engineering background, the equivalent elasticity problem was analyzed by age‐adjusted effective modulus method, and vertical deformation formula was deduced. A simplified model and a refined model of structure were established. The correctness of the deformation formula and modeling had been proven by comparing the dynamic characteristics and numerical simulation results. Based on the simplified model, the optimal construction plan of the conjoined super high‐rise structure was discussed. Based on the deformation formula, the predeformation calculation method of the conjoined super high rise was studied, and the correctness was verified by numerical simulation. The results show that the largest vertical deformation of the connected structure occurs at the position of corridor, and an apparent mutation occurs here. Properly delaying the rigid connection timing between corridor and tower is beneficial to the control of the overall structural deformation difference and internal force. The predeformation analysis method proposed in this paper is correct and effective, which could offset the vertical deformation of the structure during the construction sequence.